La responsabilité sociale des universités en France : un concept en émergence ? - Emmanuelle Annoot (Presses universitaires de la Méditerranée, 2012)
Recent reforms have strengthened the links between French universities and their hinterland. Public powers and associations play a major role in supporting the development policies of these institutions. Autonomous universities are acknowledged as major social, economic and cultural actors in their environments. Such orientations have changed the place of universities in society. Their social responsibility is mentioned as soon as they meet the needs of the local populations in terms of social and cultural life. More especially, access to higher education, relevant curricula contribute to enhance their role as part of the public service. The impact of the autonomy of universities on a democratic access to higher education remains to be studied at a local, national and European scale.